Analysis of the Variation in Salaries of Employees of Government Ministries in Iraq by Using of The Lorenz Curve and The Gini Coefficient*H. - Mahdi , Haider Khadim (South Asian Journal of Social Sciences and Humanities, 2024)
The disparity in the distribution of income is one of the main reasons for the failure to achieve social justice among members of society, which creates an unhealthy environment for workers in government sectors and institutions and also works to reduce the quality of work and lower the level of productivity. Conversely, reducing disparity leads to increased productivity and creates a suitable environment. It contributes to increasing productivity rates and improving the quality of institutional performance. The research discussed an important topic related to the extent of the discrepancy between the salaries of employees in Iraqi government institutions using the Lorenz curve and the Gini coefficient through a presentation of the research problem, which is the extent of the discrepancy in the salaries of state employees according to the approved salary scale, and what impact this has on social justice in the distribution of income, assuming that the adoption of A salary scale set by the authorities is based on reducing financial disparities between state employees with equal qualifications, such as educational attainment and work tasks, and reduces disparities of discrimination between workers in various government sectors and achieves social justice in income distribution. The research concluded that the actual distribution curve was very close to the symmetry line curve, in addition to the presence of a very small gap between the two lines, which indicates fairness in the distribution of monthly salaries among workers in government ministries who are in the fourth degree/first stage of the approved salary scale. The value of the Gini coefficient complementary to the work of the Lorenz curve was about (0.4), which means that the value of the Gini coefficient is close to zero. This indicates that the distribution of salaries of employees of government ministries is close to equitable distribution.